Rethinking the Political Economy of Decentralization: How Elections and Parties Shape the Provision of Local Public Goods - Ponce Rodríguez, Raúl Alberto (2018)
As more and more of the world’s states devolve power and resources to sub-national governments, decentralization has emerged as one of the most important global trends of the new century. Yet, there is still no consensus as to the benefits of decentralization and how to design institutions that can realize these benefits. We investigate the political conditions under which the decentralization of authority will improve the delivery of public goods. Building off Oates’ “decentralization theorem” to include inter-jurisdictional spillovers, we develop a new theory suggesting that the interaction of democratic decentralization (the popular election of sub-national governments) and party centralization (the power of national party leaders over sub-national office-seekers) will produce the best service delivery outcomes. To test this argument empirically, we develop a new dataset of sub-national political institutions. Our analyses, which examine educational and health service delivery in 135 countries across thirty years, provide support for our theoretical expectations.